Al-Fikru Al-Dini Fi Masyrui Muassasati Mu'minuna Bila Hududin: Qiroati Nadqoiyati - Mohamed, Hirreche Baghdad (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2022)
The religious phenomenon becomes a subject of reflection from the moment it is practiced by human beings, because it must be understood, explained and interpreted ... The revelation, the rituals and the teachings ... are fixed in sacred texts , these are the object of conservation, reading and questioning. And because the contexts in which they evolve and develop are historical, this constantly poses the modalities of harmonization and application of the texts and the way of living the faith in the present without completely breaking with the faith of the first founders, which leads to "renewal". Religious thought in Islam is part of this logic and in the contexts of this time; the Islamic religion becomes the object of research and studies in many disciplines of the human and social sciences in a critical way that has encountered an end to many postulates. More than that, religion is the main subject of many research institutions, as is the case for the Mominoun without borders Foundation, which today appeals to many Arab and Muslim academics in order to carry out its studies and studies. In our article, we opted for an approach to religious thought based on the Foundation's project. Our critical reading is devoted to the most important forum organized by the Foundation in 2014 in Marrakech.